Effects of different protein levels on growth performance and body composition of spotted scat, Scatophagus argus - Dieu Vo; Thanh Duc Nguyen; Hang Thi Thuy Tran; Hung Duc Pham; Huy Van Nguyen (Fisheries and Aquatic Sciences)
A 60-day experiment was undertaken in circle plastic tanks with a volume of 0.2 m3 using a separate circulating filtration system at 400 L/h to determine the optimal dietary protein level for the growth performance, protein efficiency rate (PER), and body composition of Scatophagus argus. Experimental diets using different materials were prepared in triplicates with different crude protein (CP) levels of 30%, 34%, 38%, and 42% which were designated as CP30, CP34, CP38, and CP42, respectively. The results showed that higher protein levels in diets increased the growth and reduced the feed conversion ratio (FCR) of fish (p < 0.05), however, no significance was found in growth rates and FCR of fish between treatment CP38 and CP42 (p > 0.05). On the contrary, PER increased with increasing the protein levels of diets from CP30 to CP38 (p < 0.05). PER was lower at 30% or 42% protein contents in the diets than that of 34% or 38% protein treatments (p < 0.05, and no significant difference in PER was found between CP34 and CP38 (p > 0.05). There were no significant differences in survival rates of fish among the treatments with more than 95% (p > 0.05). The second order polynomial regression analysis showed that the optimal dietary protein level of spotted scat was 43.7% (R2 = 0.96). Further studies about amino acids of the diets as well as body compositions should be conducted to elucidate for better dietary formulation of S. argus.